PENERAPAN RISK BASED INTERNAL AUDITING: STUDI KASUS PADA PLAN INTERNATIONAL INDONESIA - Anitaria Siregar; Siti Nurwahyuningsih Harahap (Universitas Katolik Indonesia Atma Jaya, 2018)
The purposes of this research is to assess risk maturity of Plan International Indonesia to determine whether Plan International Indonesia could implement the Risk Based Internal Auditing (RBIA) approach. Methodology which is used is descriptive methodology with qualitative approach. The Institute of Internal Auditors (2014) suggests the factors that can be taken into account when doing the assessment of risk maturity, and these factors are used for doing the assessment on this research. The result of this research shows the risk maturity of Plan International Indonesia is risk managed stage which mean Plan International Indonesia is ready to implement the RBIA approach. Risk managed also has the meaning that risk register of Plan International Indonesia can be used as the base for the audit planning in this approach. The audit strategy that will be used are management view of risk drives audit plan, assurance being given for the risk management and mitigation, and consulting service to improve risk management. Audit internal team needs to improve their capacity before implementation of this approach and also communication and socialization must be done to entire organization.